The role of reflection during the first teaching experience of foreign languag pre-service teachers: an exploratory-case study - Cote Parra, Gabriel (Colombian Applied Linguistics Journal, 2012)
This qualitative study engaged four foreign language student teachers in a reflective practice while completing their practicum. The classrooms of four educational institutions comprised the study sites: two public high schools, one private primary school and one public university, all located in a northwestern Colombian town. The researchers gathered data through student teachers’ reflective journals, one-on-one interviews and classroom observations. Findings revealed that reflection on action and reflections in action (Schön, 1987) enabled participants to redirect teaching processes. In regards to Van Manen’s (1977) three levels of reflection, this study found that although all the student teachers reached the first and second level of reflection, only two participants reached the third level, critical reflection.